The Effect Of Fig Supplementation On Nutritional Status And Immunity Of The Elderly: A Literature Review - Rachmat Faisal Syamsu; Salsabila Tirta Aprilia; Mutiara Amalia (Sean Institute, 2024)
Nutritional and immunity issues in the elderly are important issues that require serious attention, considering that as age increases, physiological changes occur that affect the nutritional status, health, and quality of life of the elderly. Factors such as reduced consumption of nutritious foods, decreased physical activity, and other health problems can increase the risk of malnutrition in the elderly. Figs ( Ficus carica ), which have long been known in traditional medicine, have been shown to have many health benefits, especially in improving the nutritional status and immunity of the elderly. The content of polyphenols, flavonoids, tannins , and other antioxidant compounds in figs has the ability to reduce oxidative stress, lower cholesterol levels, and increase endurance. Therefore, fig supplementation can be a good choice to support the health of the elderly, both in maintaining balanced nutrition and improving the body's immune system. Thus, figs are not only useful as a source of additional nutrition, but can also play a role in preventing or reducing various health problems that are often experienced by the elderly. As a medicinal plant, figs offer a more natural and economical alternative in supporting the welfare of the elderly, especially in improving the quality of life of those who are getting older.